Phytochemical screening, phenolic and flavonoid content, and antioxidant activity of Rhizophoraceae methanol extracts from Langsa, Aceh, Indonesia - INDRIATY INDRIATY; DJUFRI DJUFRI; BINAWATI GINTING; KARTINI HASBALLAH (Society for Indonesian Biodiversity, 2023)
Abstract. Indriaty, Djufri, Ginting B, Hasballah K. 2023. Phytochemical screening, phenolic and flavonoid content, and antioxidant activity of Rhizophoraceae methanol extracts from Langsa, Aceh, Indonesia. Biodiversitas 24: 2865-2876. Bruguiera cylindrica (L.) Blume,Bruguiera gymnorrhiza (L.) Lam., Ceriops decandra (Griff.) Ding Hou, Rhizophora apiculate Blume, and Rhizophora mucronata Lam. are mangrove plant species belonging to Rhizophoraceae that have been used as medicinal plants. Studies on phytochemical screening and bioactivity of Rhizophoraceae mangrove plants from the Aceh region are still limited. This study aimed to analyze the chemical compounds in Rhizophoraceae from Aceh and determine total phenolic content (TPC), flavonoid content (TFC), and antioxidant activity. The chemical compounds were determined using qualitative assay, TLC, and Gas Chromatography-Mass Spectrophotometry (GC-MS). The antioxidant activity was tested against 2,2-diphenyl-1-picrylhydrazyl (DPPH). Twenty extracts from various plant parts of Rhizophoraceae (roots, bark, leaves, and fruit/hypocotyl) were used in this study. The phytochemical screening of Rhizophoraceae plants revealed the presence of alkaloids, flavonoids, phenolics (tannins), terpenoids, steroids, and saponins. The highest TPC content was obtained from the bark of R. mucronata (484.39 mg GAE/g extract). Furthermore, the highest TFC was found in the leaves of R. apiculata ( 15.23 mg QE/g extract). Nineteen extracts had very high antioxidant activity (IC50: 2.35 ± 0.01 - 29.84 ± 0.19 µg/mL). The bark and roots of C. decandra had the most potent antioxidant activity (IC50: 2.35 0.01 and 3.23 0.01 µg/mL, respectively). The GC-MS revealed the presence of pyrocatechol (15.85%), antiarol (1.44%), and hexadecanoic acid (1.69%), that act as antioxidants. Therefore, it can be concluded that the Rhizophoraceae methanol extract contains phenols in the stem bark and flavonoids in the leaves with very high antioxidant activity as a good source of natural ingredients for future pharmaceutical product development. It is highly recommended to do further research to obtain pure compounds from these plants.